חינוך, CHINUCH: ISRAEL’S EDUCATION SYSTEM AND QUESTIONS OF IDENTITY - Arief S. Arman, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
Albeit in a different context, Wiesel’s soliloquy resonates with the pressing questions on the formation of identity, and contingent quest for meaning for many Jews. Indeed, what are the right questions to ask the divine, in as much as the divine seems to be indifferent to the indignation suffered by Jews, especially when it comes to the memory of the Shoah (?) The space to ask such questions sets itself in the rigmarole of the everyday, and ties in with notions of belonging and memory. These concepts are thus linked to the theme of religion in global politics, exemplified in the curious case of Israel. Prior to its establishment in 1948, the founders of Israel often applied religious justifications for its creation and subsequent existence, with a ‘return to homeland’ among the oft-heard sentiments. The purposes of this paper are varied. The first is to understand the character of Israel through the theoretical framework provided by Rogers Brubaker in his ‘Four Approaches to Nationalism’, with a focus on how nationalism itself can be argued as a form of religion. Secondly, we will look at the justifications to why secular education – as an extension on nationalism as religion – has taken root in Israel. We proceed with an argument that the removal of religious knowledge (primarily ethics) from the Israeli education system will prove to be detrimental in the long run, as the relationship between individuals will thus be determined purely in the language of capital, and ‘success’ as defined by market forces, which runs counter to genuine solidarity.